Before Landing: How Do New European Emigrants Prepare Their Departure and Imagine Their Destinations? - Coletto, Diego (2019)
In migration studies, the preparation for the departure of people who decide to migrate has seldom been addressed as a distinct topic. This article aims at investigating how European migrants who moved or plan to move to another European country prepare their departure. It analyses stories of migrants who move from Italy, Spain, Romania, and Bulgaria. More specifically, attention is focused on departure preparation in order to investigate what migrants do before they depart and how the free mobility of work is perceived by Europeans and applied to their migration plans. Different from general statements about European integration and belonging or about obstacles to intra-EU mobility, the analysis of what individuals do in order to get ready to leave their country of origin provides a very realistic idea of how people perceive European Union and the mobility within it.